Prevalence and Clinical Correlations of Somatostatin Receptor-2 (SSTR2) Expression in Neuroblastoma. Issue 3 (April 2019) - Alexander, Natasha; Marrano, Paula; Thorner, Paul; Naranjo, Arlene; Van Ryn, Collin; Martinez, Daniel; Batra, Vandana; Zhang, Libo; Irwin, Meredith S.; Baruchel, Sylvain
Abstract : Alternative radiolabeled, targeted agents are being investigated for children with relapsed neuroblastoma (NB) who do not respond to I 131 -metaiodobenzylguanidine (MIBG) therapy. (DOTA 0 -Tyr 3 )-octreotate targets somatostatin receptors (SSTRs), particularly SSTR2, which are expressed on NB cells. We investigated SSTR2 expression in NB tumors (36 high-risk [HR]; 33 non-HR patients) and correlated SSTR2 levels with clinical features, norepinephrine transporter (NET) expression, and MIBG avidity. SSTR2 and NET immunohistochemistry scores (0 to 3) were calculated on biopsies using digital image analysis based on staining intensity and distribution. Clinical data were correlated with SSTR2 expression. Median SSTR2 score for 69 patients was 1.31 (0.26 to 2.55). Non-HR NB was associated with a higher SSTR2 score ( P =0.032). The SSTR2 expression did not correlate with age, International Neuroblastoma Staging System (INSS) stage, MYCN amplification and histology. Higher SSTR2 scores were observed in MIBG-avid versus MIBG-nonavid NB. SSTR2 score was not significantly associated with NET score ( r =−0.062, P =0.62). Twenty-six patients who relapsed or progressed had a median SSTR2 score of 1.33 (0.26 to 2.55). Patients with NB including relapsed or progressive disease showed SSTR2 expression at diagnosis, suggesting they could be candidates for radiolabeled–DOTA-conjugated peptide imaging or therapy.